Survival of Dopaminergic Amacrine Cells after Near-Infrared Light Treatment in MPTP-Treated Mice. (30th May 2012) - Peoples, Cassandra; Shaw, Victoria E.; Stone, Jonathan; Jeffery, Glen; Baker, Gary E.; Mitrofanis, John
Abstract : We examined whether near-infrared light (NIr) treatment (photobiomodulation) saves dopaminergic amacrine cells of the retina in an acute and a chronic 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) mouse model of Parkinson disease. For the acute model, BALB/c mice had MPTP (100 mg/kg) or saline injections over 30 hours, followed by a six-day-survival period. For the chronic model, mice had MPTP (200 mg/kg) or saline injections over five weeks, followed by a three-week-survival period. NIr treatment was applied either at the same time (simultaneous series) or well after (posttreatment series) the MPTP insult. There were four groups within each series: Saline, Saline-NIr, MPTP, and MPTP-NIr. Retinae were processed for tyrosine hydroxylase (TH) immunochemistry, and cell number was analysed. In the MPTP groups, there was a significant reduction in TH + cell number compared to the saline controls; this reduction was greater in the acute ( ~ 50%) compared to the chronic ( ~ 30%) cases. In the MPTP-NIr groups, there were significantly more TH + cells than in the MPTP groups of both series ( ~ 30%). In summary, we showed that NIr treatment was able to both protect (simultaneous series) and rescue (posttreatment series) TH + cells of the retina from parkinsonian insult.